Voice Cloning With Artificial Intelligence For Commercialization Is Reviewed From Article 113 Of Law Number 28 Of 2014 Concerning Copyright - Prasetyo, Bagas Andika Mega; Fahrazi, Mahfud; Yoel, Siciliya Mardian (Jurnal Ragam Pengabdian, 2026)
The legal issue in this study focuses on the unclear criminal law regulation of artificial intelligence-based voice cloning practices used for commercial purposes, especially in relation to Article 113 of Law Number 28 of 2014 concerning Copyright. The practice of voice cloning raises issues regarding the legal status of cloned voices as well as legal protection for the original voice owner as performers. This study aims to analyze the legal status of voice cloning from the perspective of the Copyright Law and assess whether the use of voice cloning for commercial purposes without permission can be subject to criminal sanctions based on Article 113 of Law Number 28 of 2014. The research method used is normative juridical law research. The results of the study show that the human voice is not a creation, but an object of Related Rights attached to the performer. The cloned voice cannot be categorized as an original creation that stands alone because it is formed based on existing human voice data, so legally it is more accurately understood as a form of transformation or derivative work of the object of the Related Rights. The use of voice cloning without the permission of the original voice owner for commercial purposes meets the elements of acts without rights, violation of economic rights, and commercial purposes. Therefore, juridically normative, the practice of voice cloning for commercial purposes can be qualified as a criminal act of copyright infringement and related rights and can be subject to criminal sanctions based on Article 113 of Law Number 28 of 2014 concerning Copyright, even though artificial intelligence technology has not been explicitly regulated in the law.